Wife's Right to Property After Divorce: An Examination of Islamic Law and Legislation in Religious Court Decisions in Yogyakarta City - Najichah (QURU’: Journal of Family Law and Culture, 2024)
Indonesia as a sovereign state pays great attention to the rights of its citizens, especially in the context of marriage between men and women, through Islamic family law. Although there are still many divorce cases, the Religious Court as a judicial institution that handles family matters for Islamic citizens, plays an important role in positioning women fairly. However, the importance of wise, intelligent, honest and highly ethical judges cannot be ignored. Judges must be able to understand and apply the law with justice to all litigants, especially in divorce cases where women's rights are often neglected. Research into court decisions is important to see the extent to which judges consider women's interests in their decisions, especially in the context of post-divorce rights that have been formulated in Indonesian Islamic family law. The focus of this research is the wife's rights to post-divorce property as regulated in the legislation, as well as the extent to which these legal products are in accordance with the principles of gender justice. This research uses a qualitative approach with a field study at the Yogyakarta Religious Court. Data were collected and analyzed descriptively analytically, describing events related to court decisions. The gender approach was used to analyze the written law as well as what was decided by the judge in the court process. The results show that the rights obtained by women after divorce in Indonesian Islamic family law, such as the right to mut'ah, the right to maintenance, the right to refuse reconciliation, the right to hadlanah, and the right to joint property, are not discriminated against based on gender. There are no signs of marginalization, subordination, double workload, negative labeling, or violence against woman in Indonesian Islamic family law.